Berberine attenuates myocardial ischemia reperfusion injury by suppressing the activation of PI3K/AKT signaling - QIN-WEI, ZHU (Exp Ther Med, 2016)
Berberine (BBR), an isoquinoline alkaloid originally isolated from the Chinese herb Coptis chinensis (Huanglian), exhibits anti-inflammatory and immunosuppressive properties. Since myocardial ischemia/reperfusion (I/R) injury is associated with an excessive immune response, the current study was conducted to investigate the impact of BBR on myocardial I/R injury, a common disorder in clinical settings. Preconditioning of Sprague-Dawley rats with BBR (100 mg/kg/day, by gavage) for 14 days prior to the induction of I/R significantly attenuated myocardial I/R injury as manifested by a reduction in the incidence of ventricular arrhythmia and the amelioration of myocardial histological changes. These effects were found to be associated with the suppression of the phosphoinositide 3-kinase/AKT signaling pathway and the subsequent reduction of the expression of interleukin (IL)-6, IL-1β, and tumor necrosis factor-α in the serum and myocardial tissue. These results indicate that BBR has the potential be an effective alternative therapy for the prevention and treatment of myocardial I/R injury in clinical practice.